A fixed point approach to the fuzzy stability of a quadratic-quartic functional equation - Choonkil, Park (Trường Đại học Đà Lạt, 2014)
Using fixed point method, we prove the Hyers-Ulam stability of the following quadratic-quartic functional equation f(x + 2y) + f(x - 2y) = 4f(x + y) + 4f(x - y) - 6f(x) + 2f(2y) - 8f(y) in fuzzy Banach spaces. Mathematics Subject Classification. 47H10, 39B52, 54E40, 46S40, 26E50.